Binary blues: Exploring beyond dichotomized gender comparisons with a theory-driven approach. (June 2023) - Pritlove, Cheryl; Angus, Jan E; Dale, Craig; Seto Nielsen, Lisa; Kramer, Marnie
The call to move beyond binary conceptualizations of gender is not new, and yet, this categorical and contrastive approach to gender analysis remains common, particularly in health sciences. It has been posited that the problem of gender dualism rests partially in the minimal interplay between theory and method. Drawing on our experiences during a qualitative study of men's and women's involvement in cardiac rehabilitation, this article provides an account of the analytic and reflexive challenges of conducting research on gender and health and explores how the careful use of theory, specifically Bourdieu's theory of practice, can facilitate a departure from narrow gender binaries. The analysis presented in this article adds to methodological writings on gender and health, offering a theory-driven process to help researchers address the fluidity of gender as lived and negotiated in the everyday social and material circumstances of men and women, particularly during times of illness.